x mũ 3 - 4x mũ 2 - 9x + 36 = 0
(x mũ 2 - 9 ) mũ 2 - ( x - 3 ) mũ 2 = 0
x mũ 3 - 3x + 2 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ( x - 5 )( x - 3 ) - ( x + 2 )( 2x - 1 ) + x2 = 5
<=> x2 - 8x + 15 - ( 2x2 + 3x - 2 ) + x2 = 5
<=> 2x2 - 8x + 15 - 2x2 - 3x + 2 = 5
<=> -11x + 17 = 5
<=> -11x = -12
<=> x = 12/11
b) -2x( x - 1 ) + ( x - 1 )( 2x + 3 ) = x + 4
<=> -2x2 + 2x + x2 + x - 3 = x + 4
<=> 3x - 3 = x + 4
<=> 3x - x = 4 + 3
<=> 2x = 7
<=> x = 7/2
Bài làm :
\(a,\left(x-5\right)\left(x-3\right)-\left(x+2\right)\left(2x-1\right)+x^2=5\)
\(\Leftrightarrow x^2-3x-5x+15-\left(2x^2-x+4x-2\right)+x^2=5\)
\(\Leftrightarrow\left(x^2-2x^2+x^2\right)+\left(-3x-5x+x-4x\right)=5-2-15\)
\(\Leftrightarrow-11x=-12\)
\(\Leftrightarrow x=\frac{12}{11}\)
\(b,-2x\left(x-1\right)+\left(x-1\right)\left(2x+3\right)=x+4\)
\(\Leftrightarrow-2x^2+2x+2x^2+3x-2x-3-x=4\)
\(\Leftrightarrow\left(-2x^2+2x^2\right)+\left(2x+3x-2x-x\right)=4+3\)
\(\Leftrightarrow2x=7\)
\(\Leftrightarrow x=\frac{2}{7}\)
Học tốt nhé
\(\cdot\left(x+1\right)^2\ge0\)
\(\Rightarrow x^2+2x+1>0\)
\(\Rightarrow2x^2+4x+2\ge0\)
\(\Rightarrow\left(3x^2+3x+3\right)-\left(x^2-x+1\right)\ge0\)
\(\Rightarrow3\left(x^2+x+1\right)\ge x^2-x+1\)
\(\Rightarrow\)\(\frac{x^2+x+1}{x^2-x+1}\ge\frac{1}{3}\) (1)
\(\cdot\left(x-1\right)^2\ge0\forall x\)
\(\Rightarrow2x^2-4x+2\ge0\)
\(\Rightarrow\left(3x^2-3x+3\right)-\left(x^2+x+1\right)\ge0\)
\(\Rightarrow3\left(x^2-x+1\right)\ge x^2+x+1\)
\(\Rightarrow\frac{x^2+x+1}{x^2-x+1}\le3\)(2)
Từ(1),(2) => đpcm
\(x^3-4x^2-9x+36=0\)
=> \(x^2\left(x-4\right)-9\left(x-4\right)=0\)
=> \(\left(x-4\right)\left(x^2-9\right)=0\)
=> \(\orbr{\begin{cases}x-4=0\\x^2-9=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=4\\x=\pm3\end{cases}}\)
\(\left(x^2-9\right)^2-\left(x-3\right)^2=0\)
=> \(\left(x^2-9+x-3\right)\left[x^2-9-\left(x-3\right)\right]=0\)
=> \(\left(x^2+x-12\right)\left(x^2-9-x+3\right)=0\)
=> \(\left(x^2+x-12\right)\left(x^2-x-6\right)=0\)
=> \(\left(x^2-3x+4x-12\right)\left(x^2+2x-3x-6\right)=0\)
=> \(\left[x\left(x-3\right)+4\left(x-3\right)\right]\left[x\left(x+2\right)-3\left(x+2\right)\right]=0\)
=> \(\left(x-3\right)\left(x+4\right)\left(x-3\right)\left(x+2\right)=0\)
=> \(\left(x-3\right)^2\left(x+4\right)\left(x+2\right)=0\)
=> \(\hept{\begin{cases}\left(x-3\right)^2=0\\x+4=0\\x+2=0\end{cases}}\Rightarrow\hept{\begin{cases}x=3\\x=-4\\x=-2\end{cases}}\)
\(x^3-3x+2=0\)
=> \(x^3-x-2x+2=0\)
=> \(x^2\left(x-1\right)-2\left(x-1\right)=0\)
=> \(\left(x-1\right)\left(x^2-2\right)=0\)
=> x = 1